Islands in the stream: from individual to communal fiber degradation in the rumen ecosystem - Moraïs, Sarah; Mizrahi, Itzhak (FEMS microbiology reviews, 2019)
The herbivore rumen ecosystem constitutes an extremely efficient degradation machinery for the intricate chemical structure of fiber biomass, thus, enabling the hosting animal to digest its feed. The challenging task of deconstructing and metabolizing fiber is performed by microorganisms inhabiting the rumen. Since most of the ingested feed is comprised of plant fiber, these fiber-degrading microorganisms are of cardinal importance to the ecology of the rumen microbial community and to the hosting animal, and have a great impact on our environment and food sustainability. We summarize herein the enzymological fundamentals of fiber degradation, how the genes encoding these enzymes are spread across fiber-degrading microbes, and these microbes' interactions with other members of the rumen microbial community and potential effect on community structure. An understanding of these concepts has applied value for agriculture and our environment, and will also contribute to a better understanding of microbial ecology and evolution in anaerobic ecosystems.